Factors Affecting the Incidence of Tinea Pedis in Palm Oil Plantation Workers in Sonomartani Village, Kualuh Hulu District, Labuhan Batu Utara Regency, Indonesia - Haryani, Sela; Riri Arisanty Syafrin Lubis; Rinna Azrida (Scientific Journal of Dermatology and Venereology, 2023)
by humid conditions, greatly affects the high incidence of tinea pedis in oil palm workers. This cannot be separated from minimal knowledge about the importance of keeping feet clean while working. This study aimed to determine the factors that influence the incidence of tinea pedis in oil palm plantation workers in Sonomartani Village, Kualuh Hulu District, Labuhan Batu Utara Regency, Indonesia. Methods: Cross-sectional observational study. A total of 48 research subjects participated in this study. Observations on sociodemographics and factors of the risk of developing tinea pedis were carried out in this study. Data analysis was carried out using SPSS univariate and bivariate. Results: The results of the study showed that age <35 years and female gender were associated with the incidence of tinea pedis, p<0.05. Personal hygiene factors such as using their own towels, washing feet after activities, and the habit of drying shoes after use are associated with the incidence of tinea pedis, p<0.05. Conclusion: The habit of washing feet and keeping shoes dry is a factor risk that contributes to the incidence of tinea pedis in oil palm plantation workers in Sonomartani Village, Kualuh Hulu District, Labuhan Batu Utara Regency, Indonesia.